On Freedom and Responsibility: Discovering the Human as a Transcendent Being - Aydin, Ciano (Religion, state & society, 2013)
This paper takes as a starting point the letter of Cardinal Angelo Sodano which is used as a preface in the various publications and translations of the Catholic Compendium of the Social Doctrine of the Church. In this letter Sodano highlights an aspect that he believes deserves special attention: ‘men and women are invited above all to discover themselves as transcendent beings, in every dimension of their lives, including those related to social, economic and political contexts’. In my philosophical investigation of this notion of transcendence I take my inspiration from an author who, although accepted as a Church Father within the Catholic Church since 1920, has not yet received much attention either within and outside the Catholic tradition: St Ephrem the Syrian. I also compare Ephrem's view of transcendence with that of St Augustine. I explain how the recognition of our own transcendence leads to the acknowledgment of a particular kind of freedom and responsibility. In order to specify these notions I also investigate their relation to the concepts of vulnerability and dignity.